IMPROVING COMMUNICATIVE LANGUAGE SKILLS THROUGH ROLE PLAYING ACTIVITY - Xojiakbarov Muhammadjon Raufjon o‘g‘li (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article is dedicated to the importance of role playing in teaching the English language to upper intermediate level learners. The most important issues needed for the organization of role play activities are looked through. The article also describes the author’s comments based on the method of observation and experience in teaching. Recommendations for the targeted organization of role-playing games are given.